ANALISA ANGKA KEHILANGAN DEBIT AIR PADA DAERAH IRIGASI (DI) WARUNGKIARA - Darmawan, Harry; Tahadjuddin, Tahadjuddin; Kartika, Nia (Prodi Teknik Sipil Fakultas Teknik Universitas Suryakancana, 2022)
ABSTRACT Water loss is the loss of a number of water discharges during the water distribution process, this makes the water distribution rate smaller than the water demand rate. This problem also occurs in the irrigation area (DI) of Warungkiara, Warungkiara District, Sukabumi Regency. The loss of a number of water discharges in water distribution makes the water distribution reach not fully reach the last channel and reach the farthest rice field. By doing this research, it is hoped that in the future it can be used as reference material for the Sukabumi Regency PSDA service in minimizing the loss of water discharge in order to maintain the availability of water discharge in the Warungkiara Irrigation Area. The irrigation area (DI) of Warungkiara has a channel length of 6.6 km with a service area of 507 hectares and gets water allocation from the Ubrug Hydroelectric Dam, which is 1 – 1.3 m3/second. Loss of water flow occurs along the channel with the largest water loss taking place in the segment into two, namely 0.141 m3/ sec ago shortage of water discharge occurred in the last line is 0146 m3/ sec. The causes of the loss of water discharge include the large number of water withdrawals without permission, distribution of excess water discharge, seepage/leakage and accumulation of sediment in the channel. The recommendations for handling water loss include conducting counseling, appeals and controlling according to the law, proposing replacement of scot beam doors, cleaning and closing channel leaks, carrying out routine mud removal, increasing the number of officers and applying for rehabilitation and improvement in channel linings. Keywords: water distribution, water loss, channel, (DI) ABSTRAK Kehilangan air ialah hilangnya sejumlah debit air disaat proses penyaluran air, hal tersebut membuat angka penyaluran air lebih kecil dari pada angka kebutuhan air. Permasalahan tersebut juga terjadi pada Daerah Irigasi (DI) Warungkiara, Kecamatan Warungkiara, Kabupaten Sukabumi. Hilangnya sejumlah debit air dalam penyaluran air membuat jangkauan penyaluran air tidak sepenuhnya sampai di saluran terakhir dan menjangkau petak sawah terjauh. Dengan dilakukannya penelitian ini diharapkan kedepannya dapat dijadikan bahan referensi untuk dinas PSDA Kabupaten Sukabumi dalam meminimalisir angka kehilangan debit air guna menjaga ketersediaan debit air pada Daerah Irigasi Warungkiara. Daerah Irigasi Warungkiara memiliki panjang saluran seluas 6.6 km dengan luas layanan 507 hektar serta mendapatkan alokasi air dari Bendungan PLTA Ubrug yaitu 1-1.3 m3/detik. Kehilangan debit air terjadi di sepanjang saluran dengan kehilangan air terbesar berlangsung di ruas ke 2 yaitu 0.141 m3/detik lalu kekurangan debit air terjadi di saluran terakhir yaitu 0.146 m3/detik. Penyebab hilangnya debit air terjadi karena banyaknya pengambilan air tanpa izin, pembagian debit air berlebih, rembesan/kebocoran dan menumpuknya sedimen di saluran. Adapun rekomendasi penanganan kehilangan air dengan cara melakukan penyuluhan, himbauan dan penertiban sesuai undang-undang, mengajukan penggantian pintu skot balok, melakukan pembersihan maupun menutup lubang kebocoran saluran, melakukan pengangkatan lumpur secara rutin, menambah jumlah personil petugas dan mengajukan rehab serta peningkatan di lining saluran. Kata kunci : penyaluran air, kehilangan air, saluran, Daerah Irigasi (DI)